A complex network approach for identifying vulnerabilities of the medium and low voltage grid. (10th February 2015) - Pagani, Giuliano Andrea; Aiello, Marco
The vision behind the smart grid promises, among other things, to bring more attention to the lower layers of the distribution network where users are gradually transforming into prosumers. Independent of this transformation, users will expect the same (or higher) level of reliability of the infrastructure. In this paper, we consider physical samples from the Dutch medium and low voltage network and we perform a topological analysis to assess their robustness. We also analyse the robustness of synthetic topologies from the literature on complex network analysis. We note how certain topologies are more robust than others and how a small increase in network average connectivity can highly improve the resilience of the distribution grid against random and targeted attacks.